PENERAPAN METODE HIERARCHICAL TOKEN BUCKET PADA JARINGAN INTERNET WARUNG JAWA - Nawawi, Renaldi Adha (Computer Based Information System Journal, 2021)
Bandwidth management is very important in a computer network concept. Bandwidth management functions to regulate network bandwidth so that each network user gets an evenly distributed bandwidth as a whole, even though there are many network users. In this Java shop, the distribution of bandwidth to each client has not been implemented. , there is no bandwidth management on the Java cafe internet network. The results of the internet speed test at the Java cafe use speedtest.net. The result is the distribution of bandwidth between client 1 and client 2 is not evenly distributed. On client 1 get download and upload speeds up to 0.65 and 1.14 Mbps. While on client 2 only get 2.9 and 1.14 Mbps, due to the absence of a bandwidth management system. Hierarchical Token Bucket (HTB) is a method of bandwidth management, HTB can provide more bandwidth to the client in a few seconds the client will get more bandwidth, the research methodology used is (Network Development Life Cycle) with a system development method for the network which includes the stages of Analysis, Design, Simulation, Implementation, Monitoring, and Management. The results show that bandwidth distribution in each client can be done with each client getting a maximum bandwidth of 768Kbps and getting a bandwidth limit-at of 268Kbps so that customers can still get an internet network even though internet traffic is heavy. . and the use of burst limit as a research method can make each client get additional bandwidth when the internet network is empty and can be accepted by clients or visitors to Java stalls.. and the use of burst limit as a research method can make each client get additional bandwidth when the internet network is empty and can accepted by clients or visitors to shop jawa..